Development of approches for targated fertilizer application in complex and variable terrains of Ethiopia - CGIAR Research Program on Water, Land and Ecosystems (2021)
Optimized and targeted fertilizer management along landscape positions results in an increased return to fertilizer investment via reducing the cost of inputs and increasing profitability of farmers; improving production efficiency with targeted fertilizer applications. The landscape targeted fertilizer application enables development agents and development partners to provide evidence-based recommendations to farmers; revitalize evidence-based decisions on targeted import of fertilizers or fertilizer blends and recommendations and thereby increasing system productivity through judicious use of fertilizers and other agronomic inputs.